Response of Casuarina equisetifolia and Casuarina junghuhniana to Elevated CO2 Levels - Buvaneswaran, C.; Edwin Raj, E.; Lalitha, S.; Warrier, Rekha R.; Jayaraj, R. S. C. (Indian Forester, 2018)
This paper discusses the response of Casuarina equisetifolia and C. junghuhniana to elevated CO2 concentrations in AOTC. In this study, three months old seedlings of Casuarina were exposed to elevated CO2 levels in open top chambers at 600 ppm and 900 ppm for a period of three months. Simultaneously, seedlings were also kept as control in open top chambers without CO2 enrichment and also in the ambient environment. Observations were made on growth parameters, dry matter accumulation, nutrient uptake and photosynthetic enzymes (RuBisCO and CA) activity. Both Casuarina equisetifolia and C. junghuhniana registered greater mean increment in height growth (73.29 and 77.25 cm in three months respectively) under high CO2 concentrations of 900 ppm when compared to control conditions (being 68.38 and 69.38 cm respectively for Casuarina equisetifolia and C. junghuhniana). The study concludes that there exists huge intra-specific variation both in Casuarina equisetifolia and C. junghuhniana, which could be exploited for future breeding programme in developing climate ready genotypes having greater potential to sequester more CO2.